NON PERFORMING LOAN, BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL, SEBAGAI PREDIKTOR LOAN TO DEPOSIT RATIO DAN RETURN ON ASSETS PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Kadek Aprilyana Sulibendika (Jurnal Ekonomi & Bisnis JAGADITHA, 2016)
The main objective in the operations of banking companies is to maximize profits / earnings. This study aims to determine the effect of non-performing loans, Operating Expenses to Operating Income, as a predictor of the Loan to Deposit Ratio and Return on Assets in corporate banking in IDX. The study population is a banking company that is in the Stock Exchange in 2009-2013. The sample was selected on the basis of the number of assets with the largest sample criteria is the criteria that the company during the observation period 2009-2013 years of the repertoire of the banking company, which amounted to 10 companies. The research data is secondary data obtained from the Indonesia Stock Exchange (www.idx.co.id) years from 2009 to 2013. Testing hypotheses of the study used path analysis technique with an application tool SPSS 17th version of the results showed that: 1) NPL significant negative effect on LDR, 2) ROA significant negative effect on LDR, 3) NPL significant negative effect on ROA, 4 ) ROA and no significant negative effect on ROA 5) LDR and no significant negative effect on ROA. 6) LDR is able to mediate between the NPL, ROA. 7) LDR is able to mediate between the ROA to ROA.